The Cardial–Epicardial Early Neolithic of Lower Rhône Valley (South-Eastern France): A Lithic Perspective - Defranould Elsa (De Gruyter, 2021)
In the lower Rhône Valley, many sites are attributed to the Early Neolithic and dated between 5600 and 4800 cal. BC. According to their ceramic production, they are associated with two cultural facies: the Cardial and the Epicardial. The relation between these two entities is still under debate (chronological, cultural or functional distinctions?). However, little is known about the lithic production of the region since the chipped stone industries are rarely evoked in the socioeconomic and cultural understanding of these first agropastoral societies. The objective of this paper is to propose a regional synthesis regarding Early Neolithic lithic industries, based on typo-technological studies of several assemblages in the Rhône Valley: The Montclus rockshelter (layers 5 to 2), the Baume de Ronze rockshelter, Le Taï and the Aigle cave. These sites are considered to be the key sites for understanding the Cardial/Epicardial complex in this area, but their lithic assemblages have never been thoroughly studied. Special attention will be given to the factors of variability or, on the contrary, to the permanence in the “schema opératoire” and we will propose explanations related to geological, functional, chronological and cultural constraints. We will also focus on lithic blade production made from honey flint and the spacialisation of “chaine opératoire” which could highlight circulation of this raw material and specialised distribution network. Finally, this synthesis is based on a renewed corpus of radiocarbon dates in order to understand this evolutionary dynamic as finely as possible.